Performance analysis of the domestic water meter park in water supply network of Ibarra, Ecuador. Issue 1 (2nd January 2017) - Szilveszter, Szabolcs; Beltran, Raul; Fuentes, Arturo
Abstract : Apparent losses are one of the most important components of non-revenue water and mainly caused by water meter under-registration. This paper studies the performance of a water meter park from a developing country water utility in Ibarra city, Ecuador. The study includes three major aspects: water meter error curve reconstruction with seven different flow rates; water meter evaluation as a function of class, manufacturer and totalized registered volume, use of two water consumption patterns for weighted error determination and their influence on water balance and performance indicators analysis. Results indicate that 44% of analyzed meters works at optimal conditions. Weighted error obtained by using two different consumption patterns indicates a 0.95% difference, which has an important impact on water balance and performance indicator results. This detailed analysis of water meters can help to develop a more efficient water meter replacement strategy and to estimate apparent water loss volume more accurately.